Innovation and Adaptation Strategies Towards The Digital Economy in Business Transformation - Lusiana, Wiwit; Mujanah, Siti; Fianto, Achmad Yanu Alif (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Information technology is developing increasingly rapidly bringing very significant changes to the economy. This technological development means that every business activity always tries to create efficiency compared to previous activities by implementing the integration of technological sophistication such as blockchain, Internet of Things (IoT) and artificial intelligence (AI). Digital business or e-business in recent digital transformation is increasingly able to attract the attention of entrepreneurs, which allows companies to immediately interact with customers, suppliers and business partners more efficiently. A more prominent focus in the transition phase from Industry 4.0 to Industry 5.0 is on innovative solutions in facing global challenges that can improve human welfare. It is an important requirement for every company to be able to strengthen strategic partnerships with external stakeholders, build a culture of innovation and improve digital skills in facing this transition phase. Therefore, this research proposes innovation and adaptation strategies in facing the transition to digital economy 5.0, which aims to create a positive impact for all parties involved as well as a sustainable and inclusive economic ecosystem.